Development of the Paragonimus heterotremus eggs and it’s larvae stages in the first intermediate host - Doanh, Pham Ngoc (Academia Journal of Biology, 2015)
The eggs of the lung fluke Paragonimus heterotremus were cultured in laboratory and experimentally infected to the first intermediate hosts. The eggs require 13-17 days in summer or 24-30 days in winter for completing the embryonation to hatch into miracidium. The miracidia are collected to expose to 5 snail species (Oncomelania sp.1; Oncomelania sp.2; Melanoides tuberculatus; Katayama nosophora and Katayama sp.). As results, only 2 species Oncomelania sp.1 and Oncomelania sp.2 are susceptible to be infected at very high rate 100% and 80.0%, respectively. Within the snail body, the larvae develop through 4 stages: sporocyt, mother redia, daughter redia and cercaria. The development time of all stages require 80-120 days. The living ability of miracidia and cercaria as well as the time at which cercaria escape from snails are also disscused.